Arterial Stiffness in Patients With Renal Transplantation; Associations With Co-morbid Conditions, Evolution, and Prognostic Importance for Cardiovascular and Renal Outcomes - Korogiannou, Maria; Xagas, Efstathios; Marinaki, Smaragdi; Sarafidis, Pantelis; Boletis, John N. (Frontiers in Cardiovascular Medicine, 2019)
Patients with chronic kidney disease (CKD), particularly those with end-stage renal disease (ESRD), are at increased risk of cardiovascular events and mortality. The spectrum of arterial remodeling in CKD and ESRD includes atheromatosis of middle-sized conduit arteries and, most importantly, the process of arteriosclerosis, characterized by increased arterial stiffness of aorta and the large arteries. Longitudinal studies showed that arterial stiffness and abnormal wave reflections are independent cardiovascular risk factors in several populations, including patients with CKD and ESRD. Kidney transplantation is the treatment of choice for patients with ESRD, associated with improved survival and better quality of life in relation to hemodialysis or peritoneal dialysis. However, cardiovascular mortality in transplanted patients remains much higher than that in general population, a finding that is at least partly attributed to adverse lesions in the vascular tree of these patients, generated during the progression of CKD, which do not fully reverse after renal transplantation. This article attempts to provide an overview of the field of arterial stiffness in renal transplantation, discussing in detail available studies on the degree and the associations of arterial stiffness with other co-morbidities in renal transplant recipients, the prognostic significance of arterial stiffness for cardiovascular events, renal events and mortality in these individuals, as well as studies examining the changes in arterial stiffness following renal transplantation.